Food handler's level of COVID-19 prevention practice and preparedness of food and drinking establishments to combat the pandemic in Eastern Ethiopia - Sisay Habte; Adera Debella; Tilahun Abdeta; Abdi Birhanu; Bikila Balis; Bajrond Eshetu; Habtamu Bekele (Frontiers Media S.A., 2022)
BackgroundFood and drinking establishments are potential hotspots for the spread of coronavirus. Food handler's have a higher risk of contracting the disease and transmitting it to others. The aim of this study was to assess the food handler's level of preventive practices toward COVID-19 and the preparedness of food and drinking establishments to tackle the pandemic in Eastern Ethiopia.MethodsThe cross-sectional study design was conducted from September 1 to 30, 2020. A stratified sampling technique was used to select 276 licensed public food and drinking establishments and a simple random sampling technique was employed to select 422 food handlers from the selected establishments. A face-to-face interview and checklist-based observation were used to collect data. The collected data were entered into Epidata 3.1 and exported to STATA version 16 for analysis. Binary logistic regression analysis were conducted to identify factors associated with COVID-19 preventive practice. Statistical significance was declared at p < 0.05.ResultsAbout 406 food handler's participated in this study, making the response rate 96.2%. The study showed that 38.4% of study participants (95% CI: 33.5, 43.1) had good preventive practices for COVID-19. Only 10.5% of food and drinking establishments fulfilled all requirements to prevent COVID-19 transmission. Being male [AOR = 0.61, 95% CI(0.61, (0.39, 0.93)], attending secondary education [AOR = 2.20, (95% CI: 1.37, 3.53)], having a favorable attitude toward COVID-19 [AOR = 1.89, (95% CI: 1.22, 2.95)], and having good knowledge about COVID-19 [AOR = 1.78, (95% CI: 1.13, 2.81)] were significantly associated with the level of COVID-19 preventive practices.ConclusionThe level of good COVID-19 preventive practice was found to be low among the food handler's. Only one in ten food and drink establishments fulfilled the national guideline for preventing COVID-19 transmission. Being male, attending secondary education, having knowledge about COVID-19, and having a favorable attitude toward COVID-19 were significantly associated with good COVID-19 preventive practices. A vibrant guideline on prevention practices should be in place at all establishments, and compliance should be monitored. Local health office experts should take comprehensive measures to make all food and drinking establishments accountable for practicing all preventive measures.